Convexity Analysis of Sequential Fractional Difference Operators Via Transference Principle - Lizama-Yanez, C (Springer Nature, 2025)
We establish new convexity results for sequential fractional differences of Riemann-Liouville type when the parameters belong to subregions of the space. Our methods are based on the transference principle. To do so, we prove transference results between three apparently different definitions of fractional differences. Our results show that the convexity is independent of the sign of the first initial value in a given subregion of Ω. © The Author(s) under exclusive licence to Korean Society for Informatics and Computational Applied Mathematics 2025.